Autochthonous Hepatitis E in Developed Countries and HEV/HIV Coinfection - Dalton, H. R.; Hunter, J. G.; Bendall, R. (Seminars in Liver Disease, 2013)
A novel hepatitis virus was long suspected as the cause of outbreaks of unexplained hepatitis with high maternal mortality in Asia. An outbreak of unexplained hepatitis in a Soviet military camp in Afghanistan led one investigator to ingest a pooled fecal extract from affected service personnel. This resulted in the discovery of the hepatitis E virus (HEV) in 1983. Subsequent studies showed that HEV was endemic in large parts of the developing world. Its incidence in industrialized nations was initially attributed to travel-related exposure. For many years after the discovery of HEV, it was considered a “new” virus, and of no relevance to developed countries. This perceived wisdom has proven to be hopelessly inaccurate. Human infections with HEV are not “new,” and are of considerable global importance, including in developed countries.
Keywords: hepatitis E virus; HEV; pork; epidemiology; human immunodeficiency virus; HIV; chronic liver disease